Effects of the plate slenderness ratio on built-up back-to-back channels stub columns - Ting, T.C.H.; Lau, Hieng Ho (Research Publishing Services, 2012)
The purpose of this paper is to investigate the influence of plate slenderness ratio on the compression capacity and the performance of cold-formed steel built-up back-to-back C-channels sections. For stub columns, the overall slenderness ratio (KL/r) of the column has little effect on the load carrying capacity of the section. However, the plate element slenderness plays a major role in determining the performance of stub columns. The plate element slenderness for web or flanges needs to be less than the yield slenderness limit to be fully effective. Otherwise, only proportion of the web or flanges can be considered as effective. The study of the effects of plate element slenderness was carried out on the cold formed steel built-up columns fabricated by connecting two lipped C-channel columns back-to-back using self-drilling screws. Experimental results are compared with the calculated design results from the NAS specifications. Finite element model was created using commercial software LUSAS v14.4 to simulate the deformation curves and also to predict the load carrying capacities. Finite element results are validated by the test results. This study on the stub column shows that the plate element slenderness plays an important role in determining the compressive capacity and behavior of the stub column.